Intermediary Politics in a Peri-Urban Village in Mangaluru, India. Issue 2 (4th May 2019) - Kadfak, Alin
Abstract: This article examines an unsettled institutional setting in a peri-urban coastal village of Mangaluru, India. This village is experiencing rapid economic, social and political changes. Urbanity has introduced formal institutions into this area as part of decentralization and state recognition to a dedicated economic development area. This peri-urban area, however, did not exist in an institutional void prior to formal recognition but under customary institutions. The newly introduced formal institutions therefore create an entangled and overlapping peri-urban governance setting. In order to understand the complex relationship between local governance bodies in swiftly urbanizing contexts, I use intermediary lens to view how institutions adapt to changing environments when becoming (formally) urban. The results show that instead of fixating performances according to mandates or laws, the formal and informal institutions both operate through intermediary performances to respond to residents' requirements and state provision of public services. To negotiate with the state, intermediaries use their skills to cultivate personal relations with local political parties, low-level bureaucrats and caste-base organizations, as well as to record vital information like demography and land relations. Furthermore, the intermediaries need to build reputation based on the perpetuation of successful representation, caste-based identity and political influence within the area. The intermediary lens illustrates a dynamic relationship between institutions influenced by current political issues and always emerging (re)alignments part of peri-urban political and economic transitions.